LOOK AT PLAUTNE'S COMEDIES (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article is devoted to the comedies of Plautus. Plautus, like other Roman comedians, was never a teacher of the audience. It was completely out of line with the traditions of the Roman republican theater, it was just entertainment. However, the author of the article proves that the play under discussion is unique in the work of the Roman poet with both the plot and all its styles. Plautus himself singles out this comedy and notes that it was not written to please the audience, like others, but to improve their morals, i.e. Plautus appears here for the only time as a teacher, unusual for the Roman stage.